Childhood and cultural diversity: a reflection on the movie "Babies"" - Ana Carolina Rocha Carneiro (Universidade Federal de Santa Catarina, 2014)
The following text aims to promote a reflection on the cultural aspects of childhood development featured in the movie "Babies" (2010), in which the growth of four babies from different nationalities until they complete one year of life is accompanied. The reflection counts on the childhood conceptions according to Campos (2008), Carvalho (2010), Christensen (2005), Corsaro (2009), Javeau (2005), Kohan (2003) and Sarmento (2004), which were related to the aspects of the movie. This text is also constituted of two axis: each one corresponds to babies represented in a rural area - Bayar in Mongolia and Ponijao in Namibia -; and in an urban space - Hattie in the United States and Mari in Japan. The movie is timeless, and it is a childhood portrait of multiple nationalities, in which the cultural diversity is part of the narrative, showing so common childhood stimulations and habits, and yet, so different. Through it an exemplification of theoretical aspects seen in practice is available, as well as it remits us to an esthetics experience. "Babies" gives a lesson of children observation and reveals how the cultural aspects and the context of these individuals should be taken into account when they are considered research subjects.